COVID-19: anxiety among hospital staff and associated factors. (1st January 2021) - Mattila, Elina; Peltokoski, Jaana; Neva, Marko H.; Kaunonen, Marja; Helminen, Mika; Parkkila, Anna-Kaisa
Abstract: Background: During the COVID-19 pandemic, hospital staff have experienced a variety of mental health challenges. European research on anxiety and stress among hospital workers during the pandemic is limited. This study aimed to describe the anxiety levels of Finnish hospital workers during the COVID-19 pandemic. Methods: The multidimensional, cross-sectional survey was distributed to all hospital staff working at two Finnish specialized medical care centres in the spring of 2020 ( n  = 1, 995). The Generalized Anxiety Disorder 7-item (GAD-7) scale was used to measure the workers' anxiety. Results: The total mean GAD-7 score was 4.88, indicating normal anxiety levels. However, 30% ( n  =  1, 079) of the respondents had mild, 10% ( n  = 194) moderate and 5% ( n  = 88) severe anxiety. Key risk factors were young age, working in a university hospital, problems in cooperation between co-workers, difficulty concentrating at work, a health-threatening physical and psychological workload, and a fear of being infected at work. Conclusion: Hospital staff experienced a variety of work-related stress and anxiety issues that should be visible to hospital administrators and policymakers alike. The anxiety is independent of whether the worker is directly involved in caring for or in any way coming into contact with COVID-19 patients. Key message: Fifty-five percent of hospital staff have normal anxiety levels. The remaining workers may need targeted support interventions, and a smaller proportion (15%) are in danger of developing longer-term problems affecting their well-being. The anxiety experienced by hospital workers during the COVID-19 pandemic is more severe than that of the population on average. If the pandemic continues, the well-being of hospital staff may be widely threatened. Despite the different geographical locations and COVID-19 situations, hospital workers in Finland and China had similar anxiety levels. The anxiety is independent of whether staff are working in the front line of managing the COVID-19 pandemic or of the number of covid-19 patients admitted to the hospital. The hospital workers felt anxiety because they were facing a new situation which causes changes in their work and daily routine. Health care employers should engage in long-term follow-up as regards the personnel's recovery from the burden caused by the pandemic and from work in general. It is necessary to make easily attainable, flexibly delivered and cost-effective treatment interventions for anxiety available to hospital staff.